AKTIVITAS ANTIOKSIDAN EKSTRAK FERMENTAT ISOLAT FUNGI ENDOFIT BIJI BUAH KENARI (Canarium indicum L.) SECARA KLT-AUTOGRAFI - Nurul Khatimah Naim; Herwin Herwin; Fitriana Fitriana; Ayyub Harly Nurung (As-Syifaa Jurnal Farmasi, 2021)
Walnut seeds (Canarium indicum L.) contain tannin, flavonoids, carotenoids which is potentially fungtioning as antioxidants. The research aimed to examine the antioxidant activity of fermentate extract of walnut seeds endophytic fungi by autography-TLC. The result of the endophytic fungi isolation in Walnut seeds (Canarium indicum L.) obtained 5 isolates with characteristics. The test result of screening free antiradical activity obtained that isolate 4th was active as an antioxidant indicated by the presence of brown spots with the addition of 1,1-diphenyl-2-picrylhydrazyl 0.004%. Isolate 4th was fermented using Maltosa Yeast Broth (MYB) medium to obtain fermentate supernatant and mycelia. The Fermentate of supernantant of isolate 4th was extracted to obtained supernantant of ethyl acetate extract. Based on the result of free antiradical activity test of ethyl acetate fermentate extract isolate 4th by autography-TLC using ethyl acetate: methanol: water eluent (6:2:1), obtained Rf 0.78 value active as free antiradical by spraying 1,1diphenyl-2-picrylhydrazil 0.004%.